Sinonasal Tract Angiosarcoma: A Clinicopathologic and Immunophenotypic Study of 10 Cases with a Review of the Literature - Nelson, Brenda L. (Humana Press Inc, 2007)
Background    Primary sinonasal tract angiosarcoma are rare tumors that are frequently misclassified, resulting in inappropriate clinical management. There are only a few reported cases in the English literature. Materials and Methods    Ten patients with sinonasal tract angiosarcoma were retrospectively retrieved from the Otorhinolaryngic Registry of the Armed Forces Institute of Pathology. Results    Six males and four females, aged 13 to 81 years (mean, 46.7 years), presented with epistaxis and bloody discharge. Females were on average younger than their male counterparts (37.8 vs. 52.7 years, respectively). The tumors involved the nasal cavity alone (n = 8) or the maxillary sinus (n = 2), with a mean size of 4.3 cm; the average size was different between the genders: males: 2.8 cm; females: 6.4 cm. Histologically, all tumors had anastomosing vascular channels lined by remarkably atypical endothelial cells protruding into the lumen, neolumen formation, frequent atypical mitotic figures, necrosis, and hemorrhage. All cases tested (n = 6) demonstrated immunoreactivity with antibodies to Factor VIII-RA, CD34, CD31, and smooth muscle actin, while non-reactive with keratin and S-100 protein. The principle differential diagnosis includes granulation tissue, lobular capillary hemangioma (pyogenic granuloma), and Kaposi’s sarcoma. All patients had surgery followed by post-operative radiation (n = 4 patients). Follow-up was available in all patients: Six patients died with disease (mean, 28.8 months); two patients had died without evidence of disease (mean, 267 months); and two are alive with no evidence of disease at last follow-up (mean, 254 months). Conclusions    Sinonasal tract angiosarcoma is a rare tumor, frequently presenting in middle-aged patients as a large mass usually involving the nasal cavity with characteristic histomorphologic and immunophenotypic features. Sinonasal tract angiosarcoma will often have a poor prognosis making appropriate separation from other conditions important.